(untitled) (Semiárida, 2018)
The triticale and durum wheat may be alternatives to stabilize and increase the grain yields, on the basis of greater water use efficiency caused in a greater tolerance to water stress. In the Agronomy Faculty of UNLPam Experimental Field, the tests were conducted for eight years, in which compared daily water consumption at different phenological stages and yield components the three species (triticale, bread and durum wheat). Triticale showed a higher grain yield than bread and durum wheat with different water availability. The strategy of triticale for improved yield was based on a larger number of grains per spike than bread and durum wheat, and a good grain weight compared to bread wheat. Also, it showed a greater water use efficiency, average of the fertilized treatments than bread and durum wheat (8,98 vs 6,97 y 5,89 kg grain ha-1 mm-1, respectively). With 300 mm of available water during the entire cycle, and distributed according to consumption required at each stage of the crop ontogeny, you can get a maximum grain yield for the conditions of the study area. In conclusion, there are non-traditional species that would increase production, improve yield stability and increase the diversity of winter crops in the semiarid central pampas.